TRANSFORMASI DIGITAL UMKM PENGRAJIN KERIPIK TEMPE DI DESA KEDUNG WARINGIN BOGOR MELALUI PEMANFAATAN MARKETPLACE - Saebani, Akhmad; Miftah, Munasiron (Bajang Institute, 2025)
One of the problems faced by Micro, Small, and Medium Enterprises (MSMEs) is the lack of digital literacy, but on the other hand, MSMEs are one of the drivers of the national economy that are resilient in various situations. This community service aims to encourage MSMEs, especially tempeh chip craftsmen in Kedung Waringin Village, Bogor, to digitally transform by utilizing the marketplace as a digital marketing tool. Tempeh chip craftsmen have so far sold their products using conventional and local methods, so that sales volume is still relatively limited. The approach taken in community service activities is through (1) socialization and identification of digital needs of MSMEs, (2) training on marketplace use, (3) assistance in account creation and product uploads, and (4) monitoring and evaluation of implementation results. Evaluation was carried out through field observations, interviews, and questionnaires before and after the activity. The results of the activity showed a significant increase in participants' digital skills and product sales volume. All of participants successfully created marketplace accounts, with an average increase in sales in the initial stage of 20-30% after diversifying online sales. Furthermore, digital literacy levels increased from 45% to 82%. This activity positively impacted business owners' confidence and independence in managing online stores independently. Overall, this activity successfully catalyzed the digital transformation of local MSMEs by utilizing marketplaces as an effective marketing tool, while simultaneously strengthening the competitiveness of traditional processed products in the digital economy